Determinants of self-employment entry: Evidence from Portugal - Simões, N.; Moreira, S.; Crespo, N. (Start-ups and SMEs: concepts, methodologies, tools, and applications, 2020)
Self-employment is increasingly an attractive labor market option worldwide. In a European context, Portugal is well-known for displaying one of the highest rates of self-employment. This study explores the main determinants of the probability to enter into self-employment in Portugal. We present results from a binary logit model using individual data drawn from national-level statistics. Our findings suggest that individuals older than 35, males, married, low educated, individuals with previous experience, and heads of household are expected to enter self-employment. The empirical study also reveals important differences regarding households’ compositions and dimensions, current and former unemployment levels, and at a regional level in Portuguese NUTS II.